2016
DOI: 10.1016/j.devcel.2016.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The Intrinsically Disordered Protein Atg13 Mediates Supramolecular Assembly of Autophagy Initiation Complexes

Abstract: Autophagosome formation in yeast entails starvation-induced assembly of the pre-autophagosomal structure (PAS), in which multiple Atg1 complexes (composed of Atg1, Atg13, and the Atg17-Atg29-Atg31 subcomplex) are initially engaged. However, the molecular mechanisms underlying the multimeric assembly of these complexes remain unclear. Using structural and biological techniques, we herein demonstrate that Atg13 has a large intrinsically disordered region (IDR) and interacts with two distinct Atg17 molecules usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
181
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(187 citation statements)
references
References 39 publications
5
181
1
Order By: Relevance
“…Some IDP binding sites become ordered upon binding to their receptor, a phenomenon called folding upon binding [12]. Several crystal and NMR structures of such complexes exist [13, 14] and they highlight details of the interactions [1518]. In terms of kinetics, these are typical examples of simple two-state reactions, where the energy landscape of the complex is presented by a very deep well and one single structure can, in essence, represent the complex.…”
Section: Introductionmentioning
confidence: 99%
“…Some IDP binding sites become ordered upon binding to their receptor, a phenomenon called folding upon binding [12]. Several crystal and NMR structures of such complexes exist [13, 14] and they highlight details of the interactions [1518]. In terms of kinetics, these are typical examples of simple two-state reactions, where the energy landscape of the complex is presented by a very deep well and one single structure can, in essence, represent the complex.…”
Section: Introductionmentioning
confidence: 99%
“…In response to nitrogen deprivation, TORC1 is inactivated, resulting in dephosphorylation of Atg13. Dephosphorylated Atg13 forms a complex with Atg1 and its regulatory complex, Atg17-Atg29-Atg31 (9), which is thought to trigger autophagosome formation (10,11). Previous reports showed that depletion of glucose, sulfate, and several amino acids also induces autophagy (7,12).…”
mentioning
confidence: 99%
“…Combining the results of Rao et al 6 and Yamamoto et al 11 in reverse chronological order along with the previous research yields a model of Atg13 function within the Atg1 complex for tethering an Atg9 vesicle (Fig. 1).…”
mentioning
confidence: 94%
“…Moreover, this activation also requires Atg17 dimerization. Both the presence of Atg13 and dimerization of Atg17 being needed for activation of the trimer are difficult to reconcile into a molecular mechanism without considering a study that was published recently by Yamamoto et al 11 Although the final model in this study does not incorporate some of the findings from the work of Rao et al, it shows that besides the previously reported 12 Atg13 binding region for Atg17 (17BR; residues 424-436), the Atg13 protein harbors an additional binding site for Atg17, named the 17LR, which is regulated by dephosphorylation of Ser379. More importantly, binding of Atg13 to Atg17 via 17LR requires dimerization of Atg17.…”
mentioning
confidence: 99%